Respostas
respondido por:
2
1) y=x²+2x+3
Δ<0 -> Não possui raiz real
X¹ = -1+
i
X² = -1-
i
-------------------------------------------------------------------------
2) y=x²+x-3
Δ=13
X¹=![\frac{-1+ \sqrt{13} }{2} \frac{-1+ \sqrt{13} }{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B-1%2B+%5Csqrt%7B13%7D+%7D%7B2%7D+)
X²=![\frac{-1- \sqrt{13} }{2} \frac{-1- \sqrt{13} }{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B-1-+%5Csqrt%7B13%7D+%7D%7B2%7D+)
Δ<0 -> Não possui raiz real
X¹ = -1+
X² = -1-
-------------------------------------------------------------------------
2) y=x²+x-3
Δ=13
X¹=
X²=
Anexos:
![](https://pt-static.z-dn.net/files/d6c/2e16bf4102883c4fe880e507398c2fea.png)
![](https://pt-static.z-dn.net/files/dc6/4cdc92f56a7e66b66a7157c77b35a4f2.png)
guilherme10001:
só falta a segunda resposta agora.
respondido por:
1
y=x²+2x+3
x²+2x+3=0
Xv=-b/2a
Xv=-2/2=-1
Yv=-Δ/4a=8/4=2
Δ=4-12
Δ=-8 (não existe raiz)
x=1⇒y=6 (1,6)
x=0⇒y=3 (0,3)
V(-1,2)
x=-2⇒y=3 (-2,3)
x=-3⇒y=6 (-3,6)
b)
y=x²+x-3
x²+x-3=0
Xv=-b/2a=-1/2
Yv=-Δ/4a=-13/4
Δ=1+12
Δ=13
para
x=0⇒y=-3 (0,-3)
V(-1/2,-13/4)
x=1⇒y=-1 (1,-1)
x=-1⇒y=-3 (-1,-3)
x=-2⇒y=-1 (-2,-1)
x²+2x+3=0
Xv=-b/2a
Xv=-2/2=-1
Yv=-Δ/4a=8/4=2
Δ=4-12
Δ=-8 (não existe raiz)
x=1⇒y=6 (1,6)
x=0⇒y=3 (0,3)
V(-1,2)
x=-2⇒y=3 (-2,3)
x=-3⇒y=6 (-3,6)
b)
y=x²+x-3
x²+x-3=0
Xv=-b/2a=-1/2
Yv=-Δ/4a=-13/4
Δ=1+12
Δ=13
para
x=0⇒y=-3 (0,-3)
V(-1/2,-13/4)
x=1⇒y=-1 (1,-1)
x=-1⇒y=-3 (-1,-3)
x=-2⇒y=-1 (-2,-1)
Anexos:
![](https://pt-static.z-dn.net/files/d02/d700d964353fa226b345963c64b997db.png)
![](https://pt-static.z-dn.net/files/daa/c36a9e239cbffa8dd74d061f4d9d546b.png)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás